Eksploring the Common Reading Difficulties in English Among Standard Six Pupils: Eksperience From Public Primary School in Tanzania - Ebby Ngonyani; Rose Ephraim Matete; Johaiven Joel Kashaigili (Research and Innovation in Social Science Education Journal (RISSEJ), 2025)
This study explored common reading difficulties among Standard Six pupils in public primary schools in Tanzania. Employing a qualitative approach with a phenomenological study design, data were collected through semi-structured interviews and focused group discussions (FGDs) involving 54 participants: seven (7) Head teachers, five (5) external school quality assurers, six (6) English teachers, and thirty-six (36) Standard Six pupils. Findings indicated that reading was a critical challenge among the pupils, particularly in areas such as fluency, decoding, comprehension, and vocabulary. Cognitive constraints, particularly memory issues, further exacerbate these difficulties. This study recommends targeted interventions, including the use of interactive instructional strategies and enhanced teaching and learning environments, such as access to learning materials and the utilization of teaching aids, to promote reading skills and memory retention among pupils.